Pengaruh Nilai Harga, Literasi Keuangan Dan Kemampuan Finansial Terhadap Minat Penggunaan Dompet Digital (ShopeePay) Dalam Transaksi Keuangan (Studi Kasus Pada Mahasiswa S1 Akuntansi Universitas Pendidikan Ganesha) - Kadek Indahyani; Rencana Sari Dewi (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aimed to determined the effect of price value, financial literacy and financial capability on the interest to use e-wallet (ShopeePay) in financial transactions, This research was quantitative research. The sample used in this study was 107 students undergraduate program accounting departement. Data from the results of questionnaires. The data analyze tehnique used in this research is multiple linear regression analysis. The results of this study show that : (1) Price Value had a positive impact and  significan on the interest to use electronic wallet (ShopeePay) in financial transactions, (2) Financial Literacy had a positive impact and significan on the interest to use electronic wallet (ShopeePay) in financial transactions, (3) Financial Capability had not a positive and  significan on the interest to use electronic wallet (ShopeePay) in financial transactions.